Strategic Planning in Co-operative Sector: A Study on Dairy - Karki, Bir Bahadur (Journal of Nepalese Business Studies, 2007)
Dairy co-operatives are found everywhere in both developed and developing countries. In developing countries, it is one of the income sources of their rural economy whereas in developed countries it takes as a sustainable business. These countries face different types of problems. Developing countries focus on increase in production volume of milk and milk product, and developed countries do on enhancement of milk product, brand, and merger of dairy co-operatives. Dairy cooperatives have been getting various opportunities as well as facing different challenges. They are going to formulate different types of strategic planning to cope with these challenges and to get success. Strategic plans of dairy cooperatives in developing countries are, generally to increase production volume of buffalo milk, bring about the internal improvement in cooperative societies, reduce cost of production, provide quality service to consumer through skill, trained and educated manpower, and e-commerce. Strategic plan of developed countries is quite different from that of developing countries. Their strategic plans are to merge different dairy cooperative societies / institutions into a dairy cooperative, and compete in the global market with quality of products.Journal of Nepalese Business Studies Vol.2(1) 2005 pp.72-80